Research on optimizing the axial force of thread connection of engine connecting rod. (December 2021) - Jia, Dewen; Cai, Cheng; Li, Yunpeng; Deng, Xiwen; Lei, Jilin; Deng, Wei; Ji, Huiping
Highlights: We put forward the accurate finite element model of thread connection. We study the influencing factors of the distribution of axial stress of the thread. We put forward the Spiralock anti-loosening thread used in engine connecting rod. Abstract: The connecting-rod (abbreviate as conrod) bolt is a key part of the crank conrod mechanism, however, due to the structural characteristics of the thread connection, uneven loading between thread teeth and stress concentration at the root of thread teeth are common. In this paper, a finite element model of the conrod bolt was established based on the mesh convergence criterion. The finite element model of the conrod bolt was verfied by Akira Yamamoto analytical method. The influence of thread pitch, pre-tightening force and thread connection length on the distribution of axial stress of the thread was studied, and the stress concentration at the first thread was more serious. To improve the stress distribution of the first thread, the Spiralock anti-loosening thread was replaced to the standard conrod bolt and taken as the research object. The results show that the axial stress distribution of the Spiralock anti-loosing thread is more uniform, the fatigue strength and life are also improved.